Antimicrobial use and incidence of multidrug-resistant Pseudomonas aeruginosa in a teaching hospital: an ecological approach Uso de antimicrobianos e incidência de Pseudomonas aeruginosa multidroga-resistente em um hospital de ensino: uma abordagem ecológica - Mariana Tresoldi das Neves; Mariana Eliza Pinto de Lorenzo; Ricardo Augusto Monteiro Barros Almeida; Carlos Magno Castelo Branco Fortaleza (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: Multidrug-resistant Pseudomonas aeruginosa is a major threat in healthcare settings. The use of antimicrobials can influence the incidence of resistant strains by direct and indirect mechanisms. The latter can be addressed by ecological studies. METHODS: Our group attempted to analyze the relation between the use of antipseudomonal drugs and the incidence of MDR-PA among 18 units from a 400-bed teaching hospital. The study had a retrospective, ecological design, comprising data from 2004 and 2005. Data on the use of four antimicrobials (amikacin, ciprofloxacin, ceftazidime and imipenem) were tested for correlation with the incidence of MDR-PA (defined as isolates resistant to the four antimicrobials of interest) in clinical cultures. Univariate and multivariate linear regression analyses were performed. RESULTS: Significant correlations were determined between use and resistance for all antimicrobials in the univariate analysis: amikacin (standardized correlation coefficient = 0.73, p = 0.001); ciprofloxacin (0.71, p = 0.001); ceftazidime (0.61, p = 0.007) and imipenem (0.87, p < 0.001). In multivariate analysis, only imipenem (0.67, p = 0.01) was independently related to the incidence of multidrug-resistant strains. CONCLUSIONS: These findings share similarities with those reported in individual-based observational studies, with possible implications for infection control. INTRODUÇÃO: Pseudomonas aeruginosa multirresistente é uma grande ameaça a pacientes nos serviços de saúde. O uso de antimicrobianos pode influenciar a incidência de isolados resistentes por mecanismos diretos e indiretos. Estudos ecológicos são indicados para avaliação conjunta desses mecanismos. MÉTODOS: Foi analisada a relação entre o uso de antimicrobianos antipseudomonas e a incidência de PAMR em 18 unidades de um hospital de 400 leitos. O estudo teve delineamento ecológico retrospectivo, abordando dados dos anos de 2004 e 2005. Dados sobre uso de quatro antimicrobianos (amicacina, ciprofloxaxina, ceftazidima e imipenem) foram testados para correlação com a incidência de PAMR (resistente aos quatro antimicrobianos de interesse). Análises univariadas e multivariadas foram realizadas por regressão linear. RESULTADOS: Na análise univarida, foram encontradas correlações significantes entre uso e resistência para os quatro antimicrobianos testados: amicacina (coeficiente de correlação padronizado = 0,73; p = 0,001), ciprofloxacina (0,71; p = 0,001), ceftazidima (0,61; p = 0,007) e imipenem (0,87, p < 0,001). Na análise univariada, somente imipenem (0,67; p = 0,01) foi relacionado de forma indepentente à incidência de PAMR. CONCLUSÕES: Esses achados apresentam semelhanças com outros obtidos em estudos observacionais de base individual, e têm implicância práticas para o controle de infecção em hospitais.